Correction: Navigating the winds of change: strategic foresight and the power of weak signals (Sustainability Science, (2026), 10.1007/s11625-025-01786-5) - Jabbour, Jason; Davidson, Debra J.; Carlsen, Henrik; King, Nicholas; Lucatello, Simone; Aricò, Salvatore; Cooke, Fang Lee; Datta, Ranjan; Gluckman, Peter; Gutierrez-Espeleta, Edgar E.; Hinwood, Andrea; Jia, Gensuo; et al. (My University, 2026)
In this article, several affiliations were incorrect: the affiliation for Simone Lucatello should have been ‘Instituto Mora-SECIHTI, Mexican Ministry for Science, Humanities and Technological Innovation, Mexico’; Nadejda Komendantova ‘International Institute for Applied Systems Analysis, Laxenburg, Austria’; Diana Mangalagiu ‘Neoma Business School, France and University of Oxford, United Kingdom’; Felix Moronta-Barrios ‘International Centre for Genetic Engineering and Biotechnology, Trieste, Italy’; Michelle Mycoo ‘The University of the West Indies, St. Augustine, Trinidad and Tobago’; Anne-Sophie Stevance ‘International Science Council, Paris, France’ The original article has been corrected.